Long‐term variation in the abundance of Pacific herring (Clupea pallasii) from the Yellow Sea in the western North Pacific and its relation to climate over the past 590 years. (13th September 2019) - Li, Haoyu; Yang, Shu; Tang, Qisheng; Zhou, Xin; Sun, Yao
Abstract: A qualitative understanding of the long‐term variation in the population dynamics of Yellow Sea (YS) herring is particularly important for clarifying the evolutionary processes and driving mechanisms of the YS large marine ecosystem. Unfortunately, because of a lack of long‐term, continuous, and simultaneous monitoring data, the specific driving processes and mechanisms of climate effects on the population dynamics of YS herring remain largely unknown. In response to this scientific issue, we preliminarily propose the idea of reconstructing long‐term changes in YS herring abundance over the past 590 years (AD 1417–2004) based on historical documents and attempt to explore the impacts of climate on the population. Our results show that YS herring abundance maintained at a relatively high level from AD 1417 to 1870 (during the Little Ice Age); in contrast, the population declined significantly from AD 1870 to 2004 at different rates. In addition, we also found that there were strong relationships between the population abundance of YS herring and the Pacific decadal oscillation (PDO) and drought/flood cycles. We suggest that the fluctuations in YS herring abundance may be influenced by ocean–climatic circulation shifts throughout the North Pacific, especially the PDO.